Ritual Olah Rasa dalam Pelaksanaan Digitalisasi Manuskrip di Masyarakat AKUR Sunda Wiwitan, Kuningan, Jawa Barat - Permadi, Tedi (Perpustakaan Nasional RI, 2024)
The Sundanese AKUR community is a community institution with a royal character and makes Paseban Tri Panca Tunggal as the center of its government. They have many manuscripts whose conditions are threatened with damage so that they need to be immediately saved physically and their contents, among others by curative preservation of digital techniques. This study was conducted with a qualitative descriptive method and aims to find out the meaning of sense in manuscript digitization activities in Paseban Tri Panca Tunggal. The approach in this study is an anthropological approach with the researcher as an active participant involved in all activities, from the planning stage to reporting to the supporting institutions. The data used are primary data, namely documents issued by AKUR Sunda, observations, and direct interviews with the extended family of AKUR Sunda. The data review is presented with descriptive techniques based on the classification of data acquisition. The conclusion is that the olah rasa or samadi is a special ritual in the AKUR Sunda Wiwitan belief. This ritual has both vertical and horizontal dimensions, a concrete relationship between humans and their God and humans with fellow God's creations. The offerings sesajen or sarandu are symbols presented in a concrete form of prayer, as an expression of gratitude and a form of request expressed to God as the ruler of the universe.